Type 2 Diabetes Mellitus (T2DM) and Carbohydrate Metabolism in Relation to T2DM from Endocrinology, Neurophysiology, Molecular Biology, and Biochemistry Perspectives. (9th August 2022) - Mills, Hilla; Acquah, Ronald; Tang, Nova; Cheung, Luke; Klenk, Susanne; Glassen, Ronald; Pirson, Magali; Albert, Alain; Hoang, Duong Trinh; Van, Thang Nguyen
Abstract : Type 2 diabetes mellitus (T2DM) is a severe disease caused by metabolic disorders, particularly carbohydrate metabolism disorders. The disease is a fatal global trouble characterised by high prevalence rates, causing death, blindness, kidney failure, myocardial infarction, amputation of lower limps, and stroke. Biochemical metabolic pathways like glycolysis, gluconeogenesis, glycogenesis, and glycogenolysis are critical pathways that regulate blood glucose levels with the glucokinase (GK) enzyme playing a central role in glucose homeostasis. Any factor that perturbs the aforementioned biochemical pathways is detrimental. Endocrinological, neurophysiological, and molecular biological pathways that are linked to carbohydrate metabolism should be studied, grasped, and manipulated in order to alleviate T2DM global chaos. The challenge, howbeit, is that, since the body is an integration of systems that complement one another, studying one "isolated" system is not very useful. This paper serves to discuss endocrinology, neurophysiology, and molecular biology pathways that are involved in carbohydrate metabolism in relation to T2DM.